2021
DOI: 10.1108/ics-06-2021-0091
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity capabilities for critical infrastructure resilience

Abstract: Purpose For many innovative organisations, Industry 4.0 paves the way for significant operational efficiencies, quality of goods and services and cost reductions. One of the ways to realise these benefits is to embark on digital transformation initiatives that may be summed up as the intelligent interconnectivity of people, processes, data and cyber-connected things. Sadly, this interconnectivity between the enterprise information technology (IT) and industrial control systems (ICS) environment introduces new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 52 publications
0
18
0
1
Order By: Relevance
“…Further insight into the first group of articles revealed that five articles developed some interesting frameworks that could be used in different scenarios in cybersecurity. These frameworks are: the Industry 4.0 maturity framework (Castelo-Branco et al, 2022), the critical infrastructure cybersecurity capability framework (Malatji, Marnewick & Von Solms, 2022), the cyber risk management framework (Lee, 2021), the experimental cyberattack detection framework (Mironeanu et al, 2021) and the IoT enabled smart government framework (Chatfield & Reddick, 2019). In addition to these frameworks, two models were proposed: the realistic-decision support model (Rodrigues et al, 2022) and the SME cybersecurity assessment model (Emer, Unterhofer & Rauch, 2021), and a model for quantifying the information security of the power network (Yuan et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Further insight into the first group of articles revealed that five articles developed some interesting frameworks that could be used in different scenarios in cybersecurity. These frameworks are: the Industry 4.0 maturity framework (Castelo-Branco et al, 2022), the critical infrastructure cybersecurity capability framework (Malatji, Marnewick & Von Solms, 2022), the cyber risk management framework (Lee, 2021), the experimental cyberattack detection framework (Mironeanu et al, 2021) and the IoT enabled smart government framework (Chatfield & Reddick, 2019). In addition to these frameworks, two models were proposed: the realistic-decision support model (Rodrigues et al, 2022) and the SME cybersecurity assessment model (Emer, Unterhofer & Rauch, 2021), and a model for quantifying the information security of the power network (Yuan et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…Studies have attempted to dissect various aspects of CSCRM, such as risk management concepts (e.g., Gani & Fernando, 2018), visibility (e.g. Kalaiarasan et al, 2022) and achieving supply chain resiliency (e.g., Malatji et al, 2021). It has been argued that most have presented conceptual frameworks without empirical data (Cheung et al, 2021).…”
Section: Cscrmmentioning
confidence: 99%
“…ICS is considered by many authors to be the heart of critical infrastructure [124], [125] because it is mainly responsible for supervisory control and data collection (SCADA), process monitoring, and control of system information flows in the industry. The importance of cybersecurity in this context has been discussed in many papers [101], [103]- [105], [114], [126]. The cluster also includes studies on software-defined networking issues, which is an important element responsible for the security of data transmitted within the network [110] and can be a countermeasure for Address Resolution Protocol (ARP) spoofing in Communication-Based Train Control (CBTC) systems [127].…”
Section: ) Fc1 -Security Of Industrial Control Systemsmentioning
confidence: 99%
“…The initially identified clusters 2, 3, 4, and 6 (see Table V) were merged into FC2 (final cluster 2) as they all pertain to the same major thematic area: implementing Industry 4.0 technologies to support critical infrastructure. It should be noted that in some of the papers, the authors observed that the main technologies of Industry 4.0 support critical infrastructure [105], [108], but in other studies technologies such as CPSs [104], (I)IoT [103], [104], cloud computing [102], [126], blockchain [103] were considered important and inseparable elements of critical infrastructure as such. In some publications, the authors explore the integration of various I4.0 technologies in the context of CI, e.g.…”
Section: Fc2 -I40 Solutions As Supportive CI Elementsmentioning
confidence: 99%
See 1 more Smart Citation